Design of an SOA-based integrated optical switch - Millett, Ronald (University of Ottawa (Canada), 2005)
This thesis describes and validates the design of an optical switch that uses a vertically-integrated active/passive waveguide in an InP-based heterostructure. The goal was to design a monolithically integrated proof-of-concept 2x2 switch for use in a reconfigurable optical add-drop module (ROADM). The 1x2 building-block used for this switch consists of a passive 3dB power splitter with two semiconductor optical amplifiers (SOAs) incorporated into each of the output arms. The major contributions are an integrated 3dB power splitter design derived from a validated general design procedure based on a reductionist approach, active waveguide modeling based on evanescent coupling to a weakly-confined SOA region for the switch function, and preliminary layout designs of 2x2 and 4x4 switch fabrics. The performance of the switch was determined through finite-element analysis using FEMLAB, based on material simulations performed using OptiHS, employing post-processing in MATLAB, and validated with beam-propagation analysis using OptiBPM.
Keywords: Engineering, Electronics and Electrical.